Vernon, Politics And The People: A Study In English Political Culture, C. 1815-1867 - Ellefson, C. Ashley (Teaching History: A Journal of Methods, 1995)
In this important though sometimes obscurely written and badly edited book, James Vernon challenges the traditional notion that the English Reform Acts of 1832 and 1867 increased the effective participation of the population in politics and argues instead that during this period "English politics became progressively less democratic." Using the five constituencies of Oldham, Tower Hamlets, Boston, Lewes, and Devon for his illustrations, Vernon shows that as the elite had to grant the demands of Englishmen for direct participation in politics, it was able to find ways to make that participation all but meaningless.